The relationship between social and gross motor skills in children with Autism Spectrum Disorder (ASD) in Greece: implications for practice - Farsari, Eleftheria; Nitsiou, Chrisa (Preschool and Primary Education, 2024)
Abstract. Children with Autism Spectrum Disorder face significant difficulties in their social and motor development. Previous research has shown that motor difficulties are associated with and may predict social impairments in young children with the Autism Spectrum Disorder (ASD). The aim of this study was to examine the relationship between the development of gross motor and social skills among children with ASD between seven and eleven years old. A cross-sectional research design was applied with a group of 31 children (21 boys-67.7%, 10 girls) with ASD, and mean chronological age 9.3 ± 1.4 years old, from four primary special education schools in Greece Social skills were assessed by the classroom teacher in charge using the Educational Evaluation Tool for Social Skills (EET-SS) in children with autism, developed by Apteslis et al. (2012), and the children’s gross motor development was measured, by the researcher using the Test of Gross Motor Development (TGMD-3) (Ulrich, 2019). Data analysis revealed that there was a moderate correlation between children’s social and gross motor skills. Additionally, the developmental age children’s scores on the TGMD-3 ball skills, were found to be associated with most of the children’s EET-SS scores. The study showed that children’s specific social skills were correlated with specific gross motor skills, such as the skills associated with object manipulation. Overall, the relationship between social skills and gross motor skills in children with ASD should be taken into consideration when designing and implementing assessment practices and educational programmes for children with ASD so that the children can improve both their gross motor skills and social skills, and ultimately the quality of their everyday functioning, in school or any other setting.